Comparison of Amritsar scoring system using quantitative contrast enhanced ultrafast magnetic resonance mammography and diffusion technique with conventional Kaiser scoring system - Kapoor, Atul; Kapur, Aprajita; Sidhu, Bholla Singh; Singh, Paramjit; Brar, Navjot; Singh, Jasdeep (International Surgery Journal, 2022)
Background: Magnetic resonance imaging (MRI) mammography has been recommended as a problem solving tool in patients with breast lump for which newer imaging protocols like abbreviated, ultrafast MRI and diffusion MRI are now available. For interpretation lexicons like BIRADS and Kaiser score system are available but there is a scope for improvement of results and need for newer lexicons. Methods: Retrospective study of 175 patients of breast lump who had MRI mammography was done. The lesions were labelled as malignant by Kaiser score system (KSS) and a newer scoring system “Amritsar score system” (AMSS). Final diagnoses was confirmed by histological examination with hormone and Her2neu receptor studies. Statistical analysis was done for correlation, sensitivity, specificity and accuracy along with area under curves and the results compared. Results: Study comprised 32/175 patients with malignant nodules. Mean age of 47.2 (range: 44.2-49.6) years with mean nodule size of 2.2 cm (range 1.8-5.5 cm). ADC and Ktrans, Kep, TTE, MS and IAUC60 showed high correlation with size of malignant nodule. Sensitivity of detection was 87.4%, 87.5%, 88.6%, 71.8% and 80% respectively for ADC, Ktrans, Kep, TTE, MS and IAUC60 while specificities were 94, 88.7, 88.7% 90% and 90% respectively. The sensitivity, specificity and accuracy for KSS and AMSS were 62.5%, 88.9%, 72% and 96.5%, 90% and 94% respectively. Conclusions: AMSS is more accurate than KSS and improves the sensitivity and specificity of cancer detection. Ktrans and ADC imaging parameters not only show high sensitivity for cancer detection but also have a good correlation with the size and nuclear grade to be used as imaging biomarkers.